Miscellaneous materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Cole, Fay-Cooper, 1881-; Gilmore, Melvin R. (Melvin Randolph), 1868-1940; Haddon, Alfred C. (Alfred Cort), 1855-1940; Edgerton, Franklin, 1885-1963; Gusinde, Martin, 1886-1969; Hallowell, A. Irving (Alfred Irving), 1892-1974; Hiller, Wesley R.; Mooney, James, 1861-1921; Nelson, Dorothy M.; Norton, Jeannette Young; Smith, Edgar F. (Edgar Fahs), 1854-1928; et al. (1904)
Materials relating to Speck's research and other professional activities. Items include Speck's notes taken during graduate work at Columbia University under Franz Boas, and utilized for his own anthropology courses at the University of Pennsylvania; Speck's miscellaneous notes comprising circa 500 bibliographic cards and reading notes sorted out by tribe and/or language, dealing with tribes and countries in which Speck did no field work [other entries of this type are to be found among the various groups of materials in the Speck collection, according to tribe]; correspondence concerning exhibits and specimens for the Chicago World's Fair and for the Exposition of Indian Tribal Arts in New York City; two letters from Boas regarding the work of the Committee on Research in Native American Languages; correspondence regarding topics such as the double-curve motif, family hunting areas, indigenous foods and cooking methods, wampum, silverwork, birch-bark technique, baskets, Speck's research and publications, the research and publications of others, obtaining indigenous material cultural specimens for Speck, purchases of indigenous material culture specimens (baskets, masks, etc.) from Speck, Speck's identification of items in the Pitt Rivers Museum at Oxford University, Speck's bibliography, and Speck's obituary; letters requesting copies of Speck's publications, or acknowledging the transmission of publications between Speck and others; copies and/or drafts of several of Speck's presentations and publications, including "Lectures on Primitive Religion," "Land Ownership Among Hunting Peoples in Primitive America and the World's Marginal Areas," "Review of Lowie's Introduction to Cultural Anthropology," and "The Double-Curve Motive in Northeastern Algonquian Art"; a bibliography of Speck's publications through 1942; rough drafts of miscellaneous papers, 1928-1948; Speck's notes on topics such as crane posture; Birket-Smith's 1946 "Plan for Circumpolar Research"; ten distribution maps for circumpolar culture traits, ...